Factors determining tax administration efficiency in Hadhramout, Yemen: Perspective of individual taxpayers - Salem Al-Harethi, Abobakr Ramadhan (2018)
Tax is one of the main sources of government revenue. However, not every national government has been able to effectively exploit this great opportunity to generate revenue. The tax is collected at a lower level because of the inefficient of tax administration in Yemen. The purpose of this study is to investigate the determinants of tax administration efficiency from the Yemeni perspective. This study is based on four variables used to determine factors that affect tax administration efficiency in Yemen. The four variables that are measured in this current study are autonomy, accountability, transparency and motivation. This study is underpinned by the goal setting theory and further supported by the governance theory. The data were collected through the distribution of questionnaires to 379 participants in Yemen. A total of 223 questionnaires were analyse using the Statistical Package for Social Sciences (SPSS) version 24. Based on multiple regression analysis and other statistical techniques, the results of the study showed significant relationship between autonomy, transparency, accountability and motivation with the efficiency of tax administration. Given the findings from the study, it is highlights several limitations and suggestions future studies that can be conducted in this scope.